2001
DOI: 10.1152/ajplung.2001.281.1.l71
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB in airway epithelial cells is dependent on CFTR trafficking and Cl channel function

Abstract: Polymorphonuclear leukocyte-dominated airway inflammation is a major component of cystic fibrosis (CF) lung disease and may be associated with CF transmembrane conductance regulator (CFTR) dysfunction as well as infection. Mutant DeltaF508 CFTR is mistrafficked, accumulates in the endoplasmic reticulum (ER), and may cause "cell stress" and activation of nuclear factor (NF)-kappaB. G551D mutants also lack Cl- channel function, but CFTR is trafficked normally. We compared the effects of CFTR mutations on the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 30 publications
10
159
1
Order By: Relevance
“…We observed that both of them were upregulated. NF-kB is well known to be activated in CF airway epithelial cells and to participate in their dysregulated inflammation [26][27][28]. We extended these findings by demonstrating for the first time to our knowledge a clear overexpression of NFkB in the pulmonary vascular structures of CF subjects who exhibited an impaired response to ACh.…”
Section: Discussionsupporting
confidence: 63%
“…We observed that both of them were upregulated. NF-kB is well known to be activated in CF airway epithelial cells and to participate in their dysregulated inflammation [26][27][28]. We extended these findings by demonstrating for the first time to our knowledge a clear overexpression of NFkB in the pulmonary vascular structures of CF subjects who exhibited an impaired response to ACh.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, this mechanism is defective in CF airway cells but can be rescued by expression of wild-type CFTR (26). These observations, together with other reports (18,(35)(36)(37)(38), suggest that CFTR may interfere with some of the signal transduction pathways initiated through receptor-ligand interactions. In this context, differential regulation of channel activity may represent a model to search for the signaling pathways that are defective in CF cells.…”
mentioning
confidence: 57%
“…9 Although the mode of inheritance defines CF as a single-gene disorder, its variable course indicates that non-inherited and inherited factors shape the manifestation of the monogenic disease, which has been acknowledged by several research groups with an investigation of CF-modifying genes. The disease is characterized by a proinflammatory state, 10 which has been described in-vitro in cell systems, [11][12][13][14][15][16] using a murine model 17 and was confirmed mostly, [18][19][20][21] albeit not exclusively, 22,23 in ex-vivo material studied from CF patients. Consequently, several studied candidate genes were derived from the field of immunity, immunology and host defense such as the cytokines IL8, [24][25][26] IL1B 25,26 and TGFB1.…”
Section: Introductionmentioning
confidence: 88%